Bioaccessibility and bioavailability of environmental semi-volatile organic compounds via inhalation: A review of methods and models. (April 2018) - Wei, Wenjuan; Bonvallot, Nathalie; Gustafsson, Åsa; Raffy, Gaëlle; Glorennec, Philippe; Krais, Annette; Ramalho, Olivier; Le Bot, Barbara; Mandin, Corinne
Abstract: Semi-volatile organic compounds (SVOCs) present in indoor environments are known to cause adverse health effects through multiple routes of exposure. To assess the aggregate exposure, the bioaccessibility and bioavailability of SVOCs need to be determined. In this review, we discussed measurements of the bioaccessibility and bioavailability of SVOCs after inhalation. Published literature related to this issue is available for 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin and a few polycyclic aromatic hydrocarbons, such as benzo[ a ]pyrene and phenanthrene. Then, we reviewed common modeling approaches for the characterization of the gas- and particle-phase partitioning of SVOCs during inhalation. The models are based on mass transfer mechanisms as well as the structure of the respiratory system, using common computational techniques, such as computational fluid dynamics. However, the existing models are restricted to special conditions and cannot predict SVOC bioaccessibility and bioavailability in the whole respiratory system. The present review notes two main challenges for the estimation of SVOC bioaccessibility and bioavailability via inhalation in humans. First, in vitro and in vivo methods need to be developed and validated for a wide range of SVOCs. The in vitro methods should be validated with in vivo tests to evaluate human exposures to SVOCs in airborne particles. Second, modeling approaches for SVOCs need to consider the whole respiratory system. Alterations of the respiratory cycle period and human biological variability may be considered in future studies. Highlights: Studies on SVOC bioaccessibility and bioavailability via inhalation are reviewed. Measurements are available for a dioxin and some polycyclic aromatic hydrocarbons. Existing modeling approaches cannot be applied to the whole respiratory system. Two main challenges are noted for future studies.